Analisis Yuridis Pengaturan Permodalan Koperasi dalam Undang-Undang Nomor 25 Tahun 1992 Tentang Perkoperasian - Luthvi Febryka Nola (Pusat Penelitian Badan Keahlian Setjen DPR RI, 2010)
Cooperatives as a form of business entities need capital to run its business. This paper discussed about the issues and the legal aspect of capital, which wa related in the act of cooperation No. 25/1992. The results of this study showed that the unclear about rules on reverse funds and the ineffectiveness of rules on bond. In addition there were problem related to the usage of the term “saving”, the distribution of reserve funds, the existence of grants and the lack of private sector role in order to promote the cooperatives effort. So, I recommended that the act of cooperatives should regulate clearly about the reserve fund. Also the abolishing rules regarding grants because it was in confilct with the principle of self-reliance in cooperative. Beside that, the involvement of private sector was highly needed to optimize the cooperatives through loans and equality capital.